Sedition law and the bloggers’ freedom of expression in Malaysia - Rajini Kumar Sreedharam,; Bavani Ramayah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The advancement of Information Technology has transformed the landscape of communication to the new medium of communication. Therefore, blog becomes one of the main communication mediums for a blogger in Malaysia. Bloggers write blog posts, share their likes and dislikes. They voice their opinions; provide suggestions, report news, and form groups in the Blogosphere. However, many bloggers were arrested and prosecuted in court under Sedition Law. This hinders the bloggers’ freedom of expression which is protected by Article 10(1) of the Federal Constitution of Malaysia. The objective of this article is to explore the impact of sedition law in the era of Information Technology for bloggers in practicing their freedom of expression in Malaysia. The qualitative research design has been adopted in analyzing three selected blogs and bloggers who were investigated and prosecuted in court. The authors submit that the Sedition Law does not override bloggers’ freedom of expression since the freedom itself is not originally absolute. This study will create awareness among bloggers on the importance of their blog information and the limitations of their freedom of expressions.